Penerapan SAK EMKM dalam Penyusunan Laporan Keuangan UMKM Menggunakan Aplikasi Accurate pada Shakila Bakery - Dwi Yani; Reni Dahar; Fitria Rahmi; Nino Sri Purnama Yanti (CV. ITTC INDONESIA, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in driving national economic growth; however, they continue to face challenges in preparing financial statements in accordance with applicable accounting standards. Limited accounting knowledge and unstructured transaction recording often result in inaccurate financial information, making it difficult to use as a basis for managerial decision-making. Shakila Bakery in Padang City is one of the MSMEs experiencing these issues, particularly in recording operational costs, measuring profit, and presenting financial statements that have not yet complied with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM).This study aims to analyze the implementation of SAK EMKM in the preparation and presentation of MSME financial statements using the Accurate application at Shakila Bakery. The research employs a descriptive qualitative approach with a case study design. The study focuses on the financial activities of Shakila Bakery, utilizing transaction data from the current accounting period. Data were collected through interviews, observations, and documentation, drawing on both primary and secondary data sources. Data analysis was conducted by comparing financial statement preparation practices with and without the use of the Accurate application based on SAK EMKM requirements.The results indicate that the implementation of the Accurate application improves the orderliness of transaction recording, enhances the completeness of financial statements, and increases compliance in the presentation of income statements and statements of financial position in accordance with SAK EMKM. The application of SAK EMKM using the Accurate application has positive implications for improving the quality of MSME financial information, supporting managerial decision-making, and enhancing financial accountability and transparency.